Growth pattern of celery by using different amount of Bokashi - Nurul Huda Hamdi (2018)
Celery is a member of family Apiacea which is known as Apium graveolens in scientific name. Celery is essential crops and basic ingredient requirement in Malaysia. It can be grown in wide range of climate. Nowadays, a lot of leaching occur and give bad impact to fertility of soil. Nutrients from chemical fertilizer in soil run off to the streams, lakes and sea affecting the aquatic species. As soil fertility decrease, the production of celeries and other crops also decrease. Soil properties can be enriched through treatment with soil amendments like Bokashi and compost. The purpose of this research is to study the response of celery plants to different dosage of Bokashi. The results showed that Treatment 3 with 4000 kg/ha of Bokashi had the greatest outputs; height, number of leaves and yields. One of the more significant findings to emerge from this study is that Bokashi generates better growth performance of celery than compost. Other than that, the net profit comparison also indicate that Bokashi were more profitable than compost. In general, the best dosage of soil amendment was Treatment 3; 4000 kg/ha.